A concise guide on the bionomics and key morphological characteristics for identifying Aedes pertinax (Grabham, 1906) – a mosquito species from neotropics - Ana L. Romero-Weaver; Michael T. Riles; Kristin Sloyer; Yoosook Lee; Lindsay P. Campbell; Bryan V. Giordano (EDIS)
Aedes pertinax is a non-invasive mosquito first described in Jamaica by Grabham in 1906. It is currently classified in the Protoculex Group. It was first identified in the U.S. in 2015; its current distribution is unknown because it is so difficult to differentiate it from other mosquito species that are morphologically similar. It has not been reported in association with humans or animal diseases, but Ae. Atlanticus, another mosquito in the Protoculex Group, is a vector of the Keystone virus and the West Nile virus, which have the potential to cause encephalitis and death. Moreover, Ae. serratus, once classified as synonym of Ae. pertinax, was reported infected with yellow fever in Brazil in 2008. Because Ae. pertinax may be a vector and because it has expanded its geographical range, it should be monitored closely. This publication provides a description of the species so that it can be identified and monitored.